Analisis Kinerja Pengiriman Data Modul Transceiver NRF24l01, Xbee dan Wifi ESP8266 Pada Wireless Sensor Network - Upik Jamil Shobrina; Rakhmadhany Primananda; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
WSN technology is the latest technology that still has many obstacles related to programming or real-time communication needs. Challenges related to real-time communication include the system must be able to adapt to the environment and noise as well as to the delay time that occurs when sending data. Therefore this research performs analysis of communication device (transceiver) which is the core of WSN node with delay test parameter, RAM memory usage and functional system test. The transceiver modules used are nRF24L01, Xbee S2 and ESP8266. This research is done by designing two nodes as sender and one receiving node. Data delivery is derived from the ADXL335 accelerometer sensor. The sending and receiving data is done simultaneously using RTC (Real Time Clock) module with send and receive time 0, 15, 30, and 45 seconds. From the test results show that nRF24L01 module is superior in terms of packet delivery and xbee has less noise and data collision, while esp8266 data packet received a lot of noise and data collision. In the delay parameter, xbee has the smallest range of 0.90 seconds to 1.09 seconds. For average memory usage on nRF24L01 over 32.00% of RAM capacity, xbee is more than 40.00% of RAM capacity and ESP8266 is more than 55.00% of RAM capacity.